Effects of glucan and eicosapetaeonoic acids on differential regulation on phenilpropanoids and mevalonic pathways during potato response to Phytophthora infestans - Henriquez, Maria A. (2012)
The effects of Phytophthora infestans glucans, eicosapentaenoic acid (EPA) and isolates of this pathogen, on the differential expression of eight genes from the phenylpropanoid and the mevalonate (Ac-MVA) pathways were analyzed in potato by semi-quantitative RT-PCR and qRT-PCR. The application of EPA had an elicitor effect in Russet Burbank (RB) and Defender (DF) in response to inoculation with a US8 isolate of P. infestans, thereby reducing symptoms of late blight. Such effect was associated with the expression of PAL-1 and PAL-2, since the latter occurred only when EPA was followed by inoculation, whereas these genes were down-regulated in individual treatments RB + EPA, RB + US8, DF + EPA, and DF + US8. The glucan fraction did not by itself suppress phenylpropanoid genes, but its combination with the pathogen resulted in a down-regulation of PAL-1, PAL-2 and CHS. The addition of the glucan fraction to the elicitor EPA, had a negative effect (RB + EPA + GL + US8) since plants showed higher disease symptoms than the ones pretreated with water then infected with US8, and in comparison with RB + EPA + US8 and RB + GL + US8. Exclusive up-regulation of 4CL in DF + US11 and of CHS in DF + EPA + GL + US8, DF + EPA + US11, DF + GL + US11 and DF + EPA + GL + US11, where late blight lesions were not detected, could be associated with potato protection against late blight. Along with previous findings in this pathosystem, these data suggest that genetic resistance in potato against P. infestans is not the result of isolated reactions against the pathogen, but rather the combination of many factors in-line with a polygenic/horizontal resistance.